Increased Expressions of OX40 and OX40 Ligand in Patients with Primary Immune Thrombocytopenia - Cui, Dawei (J Immunol Res, 2019)
BACKGROUND: OX40, which is also known as tumor necrosis factor receptor superfamily member 4 (TNFRSF4), and its ligand (OX40L) play a critical role in the pathogenesis of autoimmune diseases. Immune thrombocytopenia (ITP), a hemorrhagic autoimmune disorder, is characterized by low platelet counts that are predominantly caused by antiplatelet autoantibodies. In this study, we firstly investigated the clinical significance of OX40 and OX40L expression in the pathogenesis of ITP in patients. METHODS: Fifty-four newly diagnosed ITP patients and 24 healthy controls (HCs) were enrolled in this study. The percentage of OX40(+)CD4(+)T cells among CD4(+)T cells was analyzed by flow cytometry, and the expression levels of OX40 and OX40L mRNA were analyzed by quantitative real-time PCR. Plasma soluble OX40L (sOX40L) levels were analyzed by ELISA, and plasma levels of antiplatelet autoantibodies were analyzed by a solid-phase technique. RESULTS: Compared with HCs, the frequencies of OX40(+)CD4(+)T cells were significantly increased in ITP patients, particularly in patients with positive antiplatelet autoantibodies compared to those with negative antiplatelet autoantibodies. The elevated frequencies of OX40(+)CD4(+)T cells were negatively correlated with low platelet counts in patients with positive antiplatelet autoantibodies. Plasma sOX40L levels in ITP patients were significantly greater than those in HCs and increased in patients with positive antiplatelet autoantibodies compared to those with negative antiplatelet autoantibodies. Plasma sOX40L levels were negatively correlated with low platelet counts in patients with positive antiplatelet autoantibodies. Additionally, the mRNA expression levels of OX40 and OX40L in PBMCs from ITP patients were also notably greater than those from HCs, and the expression levels of OX40 and OX40L were significantly different in ITP patients with positive and negative antiplatelet autoantibodies. CONCLUSION: These data indicated that increased expression levels of OX40 and OX40L were involved in the pathogenesis of ITP, and OX40 and OX40L may be valuable therapeutic targets for ITP.